The effect of a 120 kg pontoon mass on the wave energy converter device due to heaving - Agung Dwi Prasetya; Dimas Suharto; Muhamad Fadhil Faali; Abdul Hamid; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2024)
The environment is negatively impacted by the use of fossil fuels as a source of electricity. Using sustainable ocean wave energy is one way to replace fossil fuels and maximize the usage of natural energy. Electrical energy is produced from mechanical energy by ocean waves. An apparatus for converting wave energy from the ocean is needed to absorb it. The wave energy converter uses the up-and-down action of a chain on a pontoon to rotate a generator, producing electrical energy. The mass of the pontoon and the force of the ocean waves that excite it both have an impact on its vertical movement. Thus, the impact of pontoon mass on the wave energy converter is examined in this research. Both a planetary gear system and one without were used in the investigation. The voltage and current obtained at a wave height of 35 cm were 2.28 Volts and 0.160 A, respectively, without the planetary gear and 160.41 Volts and 13.95 A, with the planetary gear. Furthermore, an evaluation of the wave energy converter machine's performance was carried out. Using a planetary gear and a wave height of 13 cm, the second experiment's minimum power production was 212.63 Watts, while the sixth experiment's maximum power output was 2237.72 Watts with a wave height of 35 cm. In the second experiment, the generator without a planetary gear produced 0.0327 watts of power with the same wave height, and in the sixth trial, the generator produced a maximum of 0.3648 watts with a 35 cm wave height. As a result, utilizing a generator with a planetary gear is preferable to using one without one